A polymer suspension for coal rock gas

By using viscosity regulators prepared by carboxymethylcellulose and amino-polyethylene glycol-lipoic acid, the degree of crosslinking of polymer suspensions is improved, and the stability and functional decline of traditional suspensions in high temperature and high salinity environments are solved, and higher viscosity, high temperature stability and salt resistance are achieved.

CN119177118BActive Publication Date: 2025-03-07山东德坤工贸有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411690014.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-07
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

Traditional polymer suspensions exhibit poor environmental adaptability in high temperature and high salinity environments, resulting in thermal degradation and functional decline of polymers, making it difficult to widely use in various coal rock types and environments.

Method used

Carboxymethylcellulose and amino-polyethylene glycol-lipoic acid are used to prepare viscosity regulators, which improves the crosslinking degree of polymer chains by forming amide bonds, and enhances the viscosity, high temperature stability and salt resistance of the suspension.

Benefits of technology

It significantly improves the viscosity, high temperature stability and salt resistance of the polymer suspension for coal rock gas, delays the thermal degradation of the polymer, and enhances its stability and functional durability in high temperature and high salinity environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of polymer suspension preparation, and relates to a polymer suspension for coal rock gas, comprising the following components in parts by weight: 0.05-0.07 parts by weight of a viscosity regulator, 0.1-0.5 parts by weight of polyacrylamide, 0.2-0.8 parts by weight of hydroxypropyl guar gum, 0.01-0.05 parts by weight of borax, 0.03-0.06 parts by weight of a polyoxyethylene octylphenyl ether surfactant, 0.02-0.05 parts by weight of a sodium hydroxide pH regulator, 0.01-0.03 parts by weight of a citric acid antiscalant, and 0.05-0.06 parts by weight of a sodium benzoate preservative. The viscosity modifier is prepared by reacting carboxymethyl cellulose and amino-polyethylene glycol-lipoic acid in a ratio of 1:1.2-1.5 and forming an amide bond under the conditions of 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide. The viscosity modifier is used to enhance the viscosity, high temperature stability and salt resistance of the suspension, thereby effectively solving the limitations of traditional suspensions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer suspension preparation, in particular to a polymer suspension for coal rock gas. Background Art

[0002] The polymer suspension for coal rock gas is a complex liquid system, mainly composed of polymer, water, and other additives. As the core component of the suspension, the polymer has excellent suspension stability and rheology, and can effectively suspend the coal rock particles in water, which is convenient for subsequent separation and purification operations. Water, as the main body of the suspension, plays a role in dispersing the coal rock particles and adjusting the viscosity of the suspension, while the additives are used to adjust the physical and chemical properties of the suspension to meet specific mining and processing requirements. The addition of polymers can significantly improve the rheology of the suspension, making the coal rock particles in the suspension more stable and easy to control and operate.

[0003] However, traditional polymer suspensions have poor environmental adaptability and are difficult to be widely used in various coal rock types and environments. When encountering high temperature and high salinity environments, the thermal degradation of the polymer is accelerated, the solubility and intermolecular interaction of the polymer are changed, and the functional decline of the polymer is caused. In view of this, a polymer suspension for coal rock gas is provided. Summary of the invention

[0004] The purpose of the present invention is to provide a polymer suspension for coal rock gas, so as to solve the problem that the traditional polymer suspension proposed in the above background technology has poor environmental adaptability and is difficult to be widely used in various coal rock types and environments. When encountering high temperature and high salinity environments, the thermal degradation of the polymer is accelerated, the solubility and intermolecular interaction of the polymer are changed, and the functional decline of the polymer is caused.

[0005] To achieve the above object, the present invention provides a polymer suspension for coal rock gas, comprising the following components in parts by weight: 0.05-0.07 parts by weight of viscosity regulator, 0.1-0.5 parts by weight of polyacrylamide, 0.2-0.8 parts by weight of hydroxypropyl guar gum, 0.01-0.05 parts by weight of borax, 0.03-0.06 parts by weight of polyoxyethylene octylphenyl ether surfactant, 0.02-0.05 parts by weight of sodium hydroxide pH regulator, 0.01-0.03 parts by weight of citric acid scale inhibitor, 0.02-0.04 parts by weight of sodium benzoate preservative, 0.01-0.03 parts by weight of chlorogenic acid anti-salt agent and 10-20 parts by weight of quartz sand proppant;

[0006] The viscosity regulator is prepared by reacting carboxymethyl cellulose and amino-polyethylene glycol-lipoic acid in a ratio of 1:1.2-1.5 and forming an amide bond under the conditions of 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide.

[0007] The specific preparation method of the viscosity modifier is as follows:

[0008] The carboxymethyl cellulose and amino-polyethylene glycol-lipoic acid are dissolved in an acetate buffer to prepare a carboxymethyl cellulose solution and an amino-polyethylene glycol-lipoic acid solution, and a magnetic stirrer is used for dissolving, and the temperature is controlled at 50-70° C. until the solution is completely dissolved. Then, 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide are added to the carboxymethyl cellulose solution, and the mixture is stirred and mixed evenly. The pH value of the solution is adjusted with an acetate buffer, and the amino-polyethylene glycol-lipoic acid is added dropwise to the mixed solution, and the stirring is continued. The reaction time is 4-6 hours. After the reaction is completed, unreacted small molecule byproducts are removed by dialysis, and a dialysis bag is used and an acetate buffer is selected as a dialysis medium for dialysis. The dialysis medium is replaced every 2-4 hours until impurities are no longer detected in the dialysate. Finally, the product is concentrated and stored by freeze drying to obtain a viscosity regulator.

[0009] Carboxymethyl cellulose is a cellulose derivative with a carboxyl (-COOH) functional group. Amino-polyethylene glycol-lipoic acid contains an amino group (-NH2). These two compounds can be linked together through an "active ester coupling" chemical reaction, with 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) as coupling agents. The specific reaction mechanism is as follows: First, EDC reacts with the carboxyl group to form an active intermediate O-acyl-N-hydroxysuccinimide ester, making it easier for the carboxyl group to undergo the next nucleophilic substitution reaction. Because the generated O-acyl-N-hydroxysuccinimide ester is easily hydrolyzed, resulting in reduced reaction efficiency, N-hydroxysuccinimide is added to stabilize the intermediate to prevent its hydrolysis and act as an auxiliary reagent to increase the efficiency and selectivity of the reaction. The activated carboxyl group then reacts with the amino-polyethylene glycol-lipoic acid of the molecule with an amino group. The amino group attacks the activated ester bond to form an amide bond and releases N-hydroxysuccinimide, ultimately forming a stable amide bond connection between carboxymethyl cellulose (CMC) and amino-polyethylene glycol-lipoic acid (NH2-PEG-LA).

[0010] As part of the polymer suspension, carboxymethyl cellulose can increase the viscosity of the aqueous solution. The increase in the viscosity of the suspension helps to keep solid particles (such as proppants) suspended in the liquid and prevent them from settling. However, under high temperature or strong acid and alkali conditions, or under high pressure conditions of drilling fluid or fracturing fluid, carboxymethyl cellulose cannot provide sufficient mechanical strength. Therefore, it is modified with amino-polyethylene glycol-lipoic acid to increase its cross-linking degree, thereby improving its viscosity, high temperature stability and mechanical properties. At the same time, the disulfide bonds of amino-polyethylene glycol-lipoic acid can coordinate with metals to improve salt resistance. In addition, amino-polyethylene glycol-lipoic acid and chlorogenic acid salt-repellents can form hydrogen bonds, further increasing the cross-linking degree of carboxymethyl cellulose, thereby increasing the thickening effect of the viscosity modifier. The thickened liquid has a better carrying capacity and can effectively bring the proppant into deeper formations to ensure effective support of the fractures.

[0011] Since some coal seams contain high-salinity groundwater, the suspension needs to maintain its effectiveness within a certain range of salinity. Chlorogenic acid can also form coordination with metal ions to resist the impact of high-salt environments on polymers.

[0012] As a further improvement of the technical solution, the mass fraction of the carboxymethyl cellulose solution is 1-5%.

[0013] As a further improvement of the technical solution, the mass fraction of the amino-polyethylene glycol-lipoic acid solution is 2-5%.

[0014] As a further improvement of the technical solution, the pH value of the acetate buffer solution is adjusted to 4.5-6.5.

[0015] As a further improvement of the technical solution, the molar ratio of the carboxymethyl cellulose to 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide is 1:1-2:1-2.

[0016] As a further improvement of the technical solution, the molecular weight cutoff range of the dialysis bag is 5000-10000Da.

[0017] As a further improvement of this technical solution, the specific preparation method is as follows:

[0018] Sodium hydroxide pH regulator is added to deionized water to adjust the pH value of the water, and then hydroxypropyl guar gum and polyacrylamide are added, and the mixture is heated and stirred at 40-50°C to dissolve for 30-60 minutes until the polymer forms a uniform solution. Borax and a viscosity regulator are added under continuous stirring, and then polyoxyethylene octylphenyl ether surfactant, citric acid scale inhibitor, sodium benzoate preservative and chlorogenic acid anti-salt agent are added in sequence. Quartz sand proppant is added under stirring, and the mixture is fully stirred to obtain a polymer suspension for coal rock gas.

[0019] As a further improvement of the technical solution, the mass fraction of the sodium hydroxide pH regulator is 1-5%, and the pH value of water is adjusted to 7-8.

[0020] As a further improvement of the technical solution, the stirring speed when the hydroxypropyl guar gum and polyacrylamide are added is 300-600 rpm, the stirring speed when the polymer forms a uniform solution is 100-300 rpm, the stirring speed when the polyoxyethylene octylphenyl ether surfactant, citric acid scale inhibitor, sodium benzoate preservative and chlorogenic acid anti-salt agent are added in sequence is 100-200 rpm, and the stirring speed when the quartz sand proppant is added is 300-600 rpm.

[0021] A stirring speed that is too high will cause excessive shearing of the polymer, resulting in polymer chain breakage, thereby reducing its thickening effect. A stirring speed that is too fast will easily introduce a large amount of air, causing excessive foam to form in the suspension, affecting subsequent operations. A stirring speed that is too low cannot ensure that all ingredients are evenly dispersed. An appropriate stirring speed can ensure that all ingredients are evenly dispersed to form a stable and consistent suspension.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] In the polymer suspension for coal rock gas, carboxymethyl cellulose and amino-polyethylene glycol-lipoic acid are used to prepare a viscosity regulator, and amino-polyethylene glycol-lipoic acid is used to increase the cross-linking degree of carboxymethyl cellulose, enhance the viscosity, high temperature stability and mechanical strength of the suspension, help to better suspend solid particles, prevent them from settling during transportation, maintain the stability of the polymer at high temperature, prevent thermal degradation, and cause functional decline of the polymer, and coordinate with the metal through disulfide bonds, thereby improving the salt resistance of the polymer, effectively solving the limitations of traditional suspensions, and at the same time, the disulfide bonds have antioxidant effects, can participate in the reaction of free radicals, thereby neutralizing free radicals and preventing oxidative damage, and help to improve the stability of the polymer suspension. In addition, the viscosity regulator can also form hydrogen bonds with the chlorogenic acid anti-salt agent to further increase the viscosity of the polymer. This synergistic effect further strengthens the viscosity regulation effect of the polymer, so that the key performance indicators of the polymer suspension are significantly improved. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] Example 1: In this example, the specific preparation method of the polymer suspension for coal rock gas is as follows:

[0026] Prepare the following components: 0.06 parts by weight of viscosity modifier, 0.5 parts by weight of polyacrylamide, 0.8 parts by weight of hydroxypropyl guar gum, 0.05 parts by weight of borax, 0.06 parts by weight of polyoxyethylene octylphenyl ether surfactant, 0.05 parts by weight of sodium hydroxide pH adjuster, 0.03 parts by weight of citric acid scale inhibitor, 0.04 parts by weight of sodium benzoate preservative, 0.03 parts by weight of chlorogenic acid anti-salt agent and 20 parts by weight of quartz sand proppant;

[0027] The viscosity modifier is prepared by reacting carboxymethyl cellulose and amino-polyethylene glycol-lipoic acid in a ratio of 1:1.2 and forming an amide bond under the conditions of 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide; the molar ratio of carboxymethyl cellulose to 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide is 1:2:2;

[0028] Dissolve carboxymethyl cellulose and amino-polyethylene glycol-lipoic acid in acetate buffer to prepare a carboxymethyl cellulose solution with a mass fraction of 5% and an amino-polyethylene glycol-lipoic acid solution with a mass fraction of 5%, use a magnetic stirrer to dissolve, control the temperature at 60°C until completely dissolved, then add 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide to the carboxymethyl cellulose solution, stir and mix evenly, adjust the pH value of the solution to 6.0 with acetate buffer, add amino-polyethylene glycol-lipoic acid dropwise to the mixed solution, continue stirring, and the reaction time is 6h. After the reaction is completed, remove unreacted small molecule by-products by dialysis, use a dialysis bag and select acetate buffer as a dialysis medium for dialysis, replace the dialysis medium every 2-4 hours, until impurities are no longer detected in the dialysate, and finally concentrate and preserve the product by freeze drying to obtain a viscosity regulator;

[0029] To deionized water, add 5% by mass of sodium hydroxide pH regulator to adjust the pH value of the water to 8, then add hydroxypropyl guar gum and polyacrylamide, heat at 50°C, stir and dissolve at 500rpm, and stir for 30 minutes until the polymer forms a uniform solution. Under continuous stirring at 300rpm, add borax and viscosity regulator, then add polyoxyethylene octylphenyl ether surfactant, citric acid scale inhibitor, sodium benzoate preservative and chlorogenic acid anti-salt agent in sequence at 100rpm, add quartz sand proppant at 600rpm, and stir thoroughly to obtain a polymer suspension for coal rock gas.

[0030] Example 2: In this example, the specific preparation method of the polymer suspension for coal rock gas is as follows:

[0031] Prepare the following components: 0.06 parts by weight of viscosity modifier, 0.5 parts by weight of polyacrylamide, 0.8 parts by weight of hydroxypropyl guar gum, 0.05 parts by weight of borax, 0.06 parts by weight of polyoxyethylene octylphenyl ether surfactant, 0.05 parts by weight of sodium hydroxide pH adjuster, 0.03 parts by weight of citric acid scale inhibitor, 0.04 parts by weight of sodium benzoate preservative, 0.03 parts by weight of chlorogenic acid anti-salt agent and 20 parts by weight of quartz sand proppant;

[0032] The viscosity modifier is prepared by reacting carboxymethyl cellulose and amino-polyethylene glycol-lipoic acid in a ratio of 1:1.4 and forming an amide bond under the conditions of 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide; the molar ratio of carboxymethyl cellulose to 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide is 1:2:2;

[0033] Dissolve carboxymethyl cellulose and amino-polyethylene glycol-lipoic acid in acetate buffer to prepare a carboxymethyl cellulose solution with a mass fraction of 5% and an amino-polyethylene glycol-lipoic acid solution with a mass fraction of 5%, use a magnetic stirrer to dissolve, control the temperature at 60°C until completely dissolved, then add 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide to the carboxymethyl cellulose solution, stir and mix evenly, adjust the pH value of the solution to 6.0 with acetate buffer, add amino-polyethylene glycol-lipoic acid dropwise to the mixed solution, continue stirring, and the reaction time is 6h. After the reaction is completed, remove unreacted small molecule by-products by dialysis, use a dialysis bag and select acetate buffer as a dialysis medium for dialysis, replace the dialysis medium every 2-4 hours, until impurities are no longer detected in the dialysate, and finally concentrate and preserve the product by freeze drying to obtain a viscosity regulator;

[0034] To deionized water, add 5% by mass of sodium hydroxide pH regulator to adjust the pH value of the water to 8, then add hydroxypropyl guar gum and polyacrylamide, heat at 50°C, stir and dissolve at 500rpm, and stir for 30 minutes until the polymer forms a uniform solution. Under continuous stirring at 300rpm, add borax and viscosity regulator, then add polyoxyethylene octylphenyl ether surfactant, citric acid scale inhibitor, sodium benzoate preservative and chlorogenic acid anti-salt agent in sequence at 100rpm, add quartz sand proppant at 600rpm, and stir thoroughly to obtain a polymer suspension for coal rock gas.

[0035] Example 3: In this example, the specific preparation method of the polymer suspension for coal rock gas is as follows:

[0036] Prepare the following components: 0.06 parts by weight of viscosity modifier, 0.5 parts by weight of polyacrylamide, 0.8 parts by weight of hydroxypropyl guar gum, 0.05 parts by weight of borax, 0.06 parts by weight of polyoxyethylene octylphenyl ether surfactant, 0.05 parts by weight of sodium hydroxide pH adjuster, 0.03 parts by weight of citric acid scale inhibitor, 0.04 parts by weight of sodium benzoate preservative, 0.03 parts by weight of chlorogenic acid anti-salt agent and 20 parts by weight of quartz sand proppant;

[0037] The viscosity modifier is prepared by reacting carboxymethyl cellulose and amino-polyethylene glycol-lipoic acid in a ratio of 1:1.5 and forming an amide bond under the conditions of 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide; the molar ratio of carboxymethyl cellulose to 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide is 1:2:2;

[0038] Dissolve carboxymethyl cellulose and amino-polyethylene glycol-lipoic acid in acetate buffer to prepare a carboxymethyl cellulose solution with a mass fraction of 5% and an amino-polyethylene glycol-lipoic acid solution with a mass fraction of 5%, use a magnetic stirrer to dissolve, control the temperature at 60°C until completely dissolved, then add 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide to the carboxymethyl cellulose solution, stir and mix evenly, adjust the pH value of the solution to 6.0 with acetate buffer, add amino-polyethylene glycol-lipoic acid dropwise to the mixed solution, continue stirring, and the reaction time is 6h. After the reaction is completed, remove unreacted small molecule by-products by dialysis, use a dialysis bag and select acetate buffer as a dialysis medium for dialysis, replace the dialysis medium every 2-4 hours, until impurities are no longer detected in the dialysate, and finally concentrate and preserve the product by freeze drying to obtain a viscosity regulator;

[0039] To deionized water, add 5% by mass of sodium hydroxide pH regulator to adjust the pH value of the water to 8, then add hydroxypropyl guar gum and polyacrylamide, heat at 50°C, stir and dissolve at 500rpm, and stir for 30 minutes until the polymer forms a uniform solution. Under continuous stirring at 300rpm, add borax and viscosity regulator, then add polyoxyethylene octylphenyl ether surfactant, citric acid scale inhibitor, sodium benzoate preservative and chlorogenic acid anti-salt agent in sequence at 100rpm, add quartz sand proppant at 600rpm, and stir thoroughly to obtain a polymer suspension for coal rock gas.

[0040] Example 4: In this example, the specific preparation method of the polymer suspension for coal rock gas is as follows:

[0041] Prepare the following components: 0.06 parts by weight of viscosity modifier, 0.1 parts by weight of polyacrylamide, 0.2 parts by weight of hydroxypropyl guar gum, 0.01 parts by weight of borax, 0.03 parts by weight of polyoxyethylene octylphenyl ether surfactant, 0.02 parts by weight of sodium hydroxide pH adjuster, 0.01 parts by weight of citric acid scale inhibitor, 0.02 parts by weight of sodium benzoate preservative, 0.01 parts by weight of chlorogenic acid anti-salt agent and 10 parts by weight of quartz sand proppant;

[0042] The viscosity modifier is prepared by reacting carboxymethyl cellulose and amino-polyethylene glycol-lipoic acid in a ratio of 1:1.4 and forming an amide bond under the conditions of 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide; the molar ratio of carboxymethyl cellulose to 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide is 1:1:1;

[0043] Dissolve carboxymethyl cellulose and amino-polyethylene glycol-lipoic acid in acetate buffer to prepare a carboxymethyl cellulose solution with a mass fraction of 5% and an amino-polyethylene glycol-lipoic acid solution with a mass fraction of 5%, use a magnetic stirrer to dissolve, control the temperature at 60°C until completely dissolved, then add 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide to the carboxymethyl cellulose solution, stir and mix evenly, adjust the pH value of the solution to 6.0 with acetate buffer, add amino-polyethylene glycol-lipoic acid dropwise to the mixed solution, continue stirring, and the reaction time is 6h. After the reaction is completed, remove unreacted small molecule by-products by dialysis, use a dialysis bag and select acetate buffer as a dialysis medium for dialysis, replace the dialysis medium every 2-4 hours, until impurities are no longer detected in the dialysate, and finally concentrate and preserve the product by freeze drying to obtain a viscosity regulator;

[0044] To deionized water, add 5% by mass of sodium hydroxide pH regulator to adjust the pH value of the water to 8, then add hydroxypropyl guar gum and polyacrylamide, heat at 50°C, stir and dissolve at 500rpm, and stir for 30 minutes until the polymer forms a uniform solution. Under continuous stirring at 300rpm, add borax and viscosity regulator, then add polyoxyethylene octylphenyl ether surfactant, citric acid scale inhibitor, sodium benzoate preservative and chlorogenic acid anti-salt agent in sequence at 100rpm, add quartz sand proppant at 600rpm, and stir thoroughly to obtain a polymer suspension for coal rock gas.

[0045] Example 5: In this example, the specific preparation method of the polymer suspension for coal rock gas is as follows:

[0046] Prepare the following components: 0.05 parts by weight of viscosity modifier, 0.5 parts by weight of polyacrylamide, 0.8 parts by weight of hydroxypropyl guar gum, 0.05 parts by weight of borax, 0.06 parts by weight of polyoxyethylene octylphenyl ether surfactant, 0.05 parts by weight of sodium hydroxide pH adjuster, 0.03 parts by weight of citric acid scale inhibitor, 0.04 parts by weight of sodium benzoate preservative, 0.03 parts by weight of chlorogenic acid anti-salt agent and 20 parts by weight of quartz sand proppant;

[0047] The viscosity modifier is prepared by reacting carboxymethyl cellulose and amino-polyethylene glycol-lipoic acid in a ratio of 1:1.4 and forming an amide bond under the conditions of 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide; the molar ratio of carboxymethyl cellulose to 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide is 1:2:2;

[0048] Dissolve carboxymethyl cellulose and amino-polyethylene glycol-lipoic acid in acetate buffer to prepare a carboxymethyl cellulose solution with a mass fraction of 5% and an amino-polyethylene glycol-lipoic acid solution with a mass fraction of 5%, use a magnetic stirrer to dissolve, control the temperature at 60°C until completely dissolved, then add 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide to the carboxymethyl cellulose solution, stir and mix evenly, adjust the pH value of the solution to 6.0 with acetate buffer, add amino-polyethylene glycol-lipoic acid dropwise to the mixed solution, continue stirring, and the reaction time is 6h. After the reaction is completed, remove unreacted small molecule by-products by dialysis, use a dialysis bag and select acetate buffer as a dialysis medium for dialysis, replace the dialysis medium every 2-4 hours, until impurities are no longer detected in the dialysate, and finally concentrate and preserve the product by freeze drying to obtain a viscosity regulator;

[0049] To deionized water, add 5% by mass of sodium hydroxide pH regulator to adjust the pH value of the water to 8, then add hydroxypropyl guar gum and polyacrylamide, heat at 50°C, stir and dissolve at 500rpm, and stir for 30 minutes until the polymer forms a uniform solution. Under continuous stirring at 300rpm, add borax and viscosity regulator, then add polyoxyethylene octylphenyl ether surfactant, citric acid scale inhibitor, sodium benzoate preservative and chlorogenic acid anti-salt agent in sequence at 100rpm, add quartz sand proppant at 600rpm, and stir thoroughly to obtain a polymer suspension for coal rock gas.

[0050] Example 6: In this example, the specific preparation method of the polymer suspension for coal rock gas is as follows:

[0051] Prepare the following components: 0.07 parts by weight of viscosity modifier, 0.5 parts by weight of polyacrylamide, 0.8 parts by weight of hydroxypropyl guar gum, 0.05 parts by weight of borax, 0.06 parts by weight of polyoxyethylene octylphenyl ether surfactant, 0.05 parts by weight of sodium hydroxide pH adjuster, 0.03 parts by weight of citric acid scale inhibitor, 0.04 parts by weight of sodium benzoate preservative, 0.03 parts by weight of chlorogenic acid anti-salt agent and 20 parts by weight of quartz sand proppant;

[0052] The viscosity modifier is prepared by reacting carboxymethyl cellulose and amino-polyethylene glycol-lipoic acid in a ratio of 1:1.4 and forming an amide bond under the conditions of 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide; the molar ratio of carboxymethyl cellulose to 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide is 1:2:2;

[0053] Dissolve carboxymethyl cellulose and amino-polyethylene glycol-lipoic acid in acetate buffer to prepare a carboxymethyl cellulose solution with a mass fraction of 5% and an amino-polyethylene glycol-lipoic acid solution with a mass fraction of 5%, use a magnetic stirrer to dissolve, control the temperature at 60°C until completely dissolved, then add 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide to the carboxymethyl cellulose solution, stir and mix evenly, adjust the pH value of the solution to 6.0 with acetate buffer, add amino-polyethylene glycol-lipoic acid dropwise to the mixed solution, continue stirring, and the reaction time is 6h. After the reaction is completed, remove unreacted small molecule by-products by dialysis, use a dialysis bag and select acetate buffer as a dialysis medium for dialysis, replace the dialysis medium every 2-4 hours, until impurities are no longer detected in the dialysate, and finally concentrate and preserve the product by freeze drying to obtain a viscosity regulator;

[0054] To deionized water, add 5% by mass of sodium hydroxide pH regulator to adjust the pH value of the water to 8, then add hydroxypropyl guar gum and polyacrylamide, heat at 50°C, stir and dissolve at 500rpm, and stir for 30 minutes until the polymer forms a uniform solution. Under continuous stirring at 300rpm, add borax and viscosity regulator, then add polyoxyethylene octylphenyl ether surfactant, citric acid scale inhibitor, sodium benzoate preservative and chlorogenic acid anti-salt agent in sequence at 100rpm, add quartz sand proppant at 600rpm, and stir thoroughly to obtain a polymer suspension for coal rock gas.

[0055] Comparative Example 1: The polymer suspension was prepared by the method of Example 2 without adding a viscosity modifier.

[0056] Comparative Example 2: The method of Example 2 was adopted, only carboxymethyl cellulose was added to the viscosity modifier, and amino-polyethylene glycol-lipoic acid modification was not adopted.

[0057] Comparative Example 3: The method of Example 2 was adopted, only amino-polyethylene glycol-lipoic acid was added to the viscosity modifier, and carboxymethyl cellulose was not modified.

[0058] The present invention prepares a polymer suspension for coal rock gas, which has good viscosity, high temperature stability and salt resistance in the application of the polymer suspension preparation technology field. The specific detection is shown in the following table:

[0059] Viscosity is an important parameter of polymer suspension, which affects the carrying capacity and fluidity of the suspension. In coal-rock gas mining, appropriate viscosity helps to maintain the stability of the bottom of the well, effectively carry drill cuttings, and ensure that the drilling fluid can circulate smoothly. The specific test steps are: clean and calibrate the Ubbelohde viscometer, and install it vertically and stably. Use a burette to inject a certain amount of polymer suspension sample into the upper spherical chamber of the Ubbelohde viscometer to avoid introducing bubbles. Close the upper valve to allow the sample to fill the lower spherical chamber. Open the upper valve to allow the sample to flow into the lower spherical chamber, release the liquid to flow through the capillary. When the sample reaches the mark line, start timing and record the time from the sample reaching the mark line to the time it completely flows out of the Ubbelohde viscometer. Repeat multiple measurements for each sample and take the average value to improve accuracy. It is also necessary to use pure solvent water for a measurement to calculate the relative viscosity. Relative viscosity (η r ) = t / t0, where t is the sample outflow time and t0 is the pure solvent outflow time. The higher the viscosity, the better the sand carrying capacity. However, if the viscosity is too high, it will lead to pumping difficulties and increase energy consumption. Therefore, the appropriate viscosity can more effectively block cracks and pores and improve work efficiency.

[0060] High temperature stability refers to the ability of a polymer suspension to maintain its original properties under high temperature conditions. In the development of deep or ultra-deep coal-rock gas reservoirs, drilling fluids and fracturing fluids often encounter high temperature environments. Therefore, it is necessary to use polymers that can withstand high temperatures without decomposition or significant performance degradation. The specific test steps are: based on the viscosity test, heat in a constant temperature oven at 150°C for 5 hours, observe and record the viscosity changes of the sample at this temperature, high temperature change rate = (relative viscosity at high temperature - initial relative viscosity) / initial relative viscosity x 100%. The lower the high temperature change rate, the better the high temperature stability.

[0061] Salt resistance refers to the ability of polymer suspension to maintain stable performance in a high-salt environment. The fluid in coal-rock gas reservoirs often contains a high concentration of salt, which will affect the stability and thickening effect of the polymer. Therefore, a polymer suspension with good salt resistance is very necessary for protecting the well wall, maintaining rheological properties and reducing corrosion. The specific test steps are: prepare a 5% calcium chloride solution by mass, mix the polymer suspension for coal-rock gas with the salt solution, and use a viscometer to measure the viscosity of each sample to evaluate the effect of salt on viscosity. The salt resistance change rate = (relative viscosity under 5% calcium chloride solution - initial relative viscosity) / initial relative viscosity x 100%. The lower the salt resistance change rate, the better the salt resistance.

[0062] The obtained data are shown in Table 1

[0063] Table 1 Performance data of Examples 1-6 and Comparative Examples 1-3

[0064]

[0065] By comparing Examples 1-6 with Comparative Examples 1-3, it can be seen that in a polymer suspension for coal rock gas, the viscosity regulator will have a significant impact on the viscosity, high temperature stability and salt resistance of the polymer suspension.

[0066] According to Examples 1-3, as the proportion of components in the viscosity modifier increases, the viscosity, high temperature stability and salt resistance of the polymer suspension for coal rock gas first increase and then decrease. This is because as the proportion of components in the viscosity modifier increases, the proportion of NH2-PEG-LA gradually increases, and the cross-linking density between polymer chains will also increase accordingly. Appropriate cross-linking can improve the viscosity and stability of the suspension, but if the cross-linking is too high, the network structure will be too tight, which will affect the fluidity of the fluid, causing the polymer network to become fragile and easy to break, thereby weakening its stability under high temperature conditions. At the same time, it will also limit the coordination ability of the active group, thereby reducing the salt resistance.

[0067] According to Example 2 and Example 4, it can be seen that with the continuous change of the content of other components in the polymer suspension, the viscosity, high temperature stability and salt resistance of the polymer suspension for coal rock gas do not change significantly. This is because the key to determining the viscosity, high temperature stability and salt resistance of the polymer suspension lies in the viscosity regulator, and the other components vary within a smaller range, which is not enough to cause significant changes in the performance of the suspension.

[0068] According to Example 2, Example 5 and Example 6, it can be seen that as the viscosity modifier content continues to change, the viscosity, high temperature stability and salt resistance of the polymer suspension for coal rock gas continue to change. This is because the change in the viscosity modifier content also means a change in the number of cross-linking points formed between polymer chains. As the viscosity modifier content increases, the interaction between the polymer chains in the suspension is enhanced, resulting in an increase in viscosity and improved high temperature stability. However, excessive cross-linking, on the contrary, causes the network structure to be too tight, thereby affecting its performance.

[0069] According to the above test experiments, Example 2 is used as the optimal example and compared with Comparative Examples 1-3 respectively.

[0070] By comparing Example 2 with Comparative Example 1, it can be seen that the viscosity, high temperature stability and salt resistance of the polymer suspension for coal rock gas are worse when no viscosity modifier is added to prepare the polymer suspension. This is because carboxymethyl cellulose and amino-polyethylene glycol-lipoic acid can increase the crosslinking between polymer chains by forming amide bonds. When no viscosity modifier is added, there are fewer crosslinks between polymer chains, resulting in lower viscosity and poorer high temperature stability of the suspension. The disulfide bonds in the viscosity modifier can coordinate with metal ions to improve the salt resistance of the suspension. In the absence of a viscosity modifier, it is easily affected by salt in a high salinity environment, so the overall performance is poor.

[0071] By comparing Example 2 with Comparative Example 2, it can be seen that when only carboxymethyl cellulose is added to the viscosity modifier without amino-polyethylene glycol-lipoic acid modification, the viscosity, high temperature stability and salt resistance of the polymer suspension for coal rock gas are worse. This is because CMC itself is a linear polymer and its viscosity regulating effect is limited. By cross-linking with NH2-PEG-LA, the interaction between polymer chains can be enhanced and the degree of cross-linking can be improved. When only CMC is added, there is a lack of additional cross-linking points, resulting in poor high temperature stability and viscosity of the suspension, insufficient salt resistance, and thus a significant decrease in the overall performance.

[0072] By comparing Example 2 and Comparative Example 3, it can be seen that the viscosity regulator only adds amino-polyethylene glycol-lipoic acid without using carboxymethyl cellulose modification, and the viscosity, high temperature stability and salt resistance of the polymer suspension for coal gas are worse. This is because CMC itself is a highly efficient thickener that can significantly increase the viscosity of the aqueous solution. Although NH2-PEG-LA can improve the performance of CMC, it does not have the same good thickening ability as CMC. CMC can still maintain a certain mechanical strength at high temperatures. The addition of NH2-PEG-LA can further enhance its thermal stability. When NH2-PEG-LA is used alone, the suspension is easily degraded under high temperature conditions, which leads to a decrease in performance.

[0073] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only preferred examples of the present invention, and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A polymer suspension for coal rock gas, characterized in that: The invention comprises the following components in parts by weight: 0.05-0.07 parts by weight of viscosity modifier, 0.1-0.5 parts by weight of polyacrylamide, 0.2-0.8 parts by weight of hydroxypropyl guar gum, 0.01-0.05 parts by weight of borax, 0.03-0.06 parts by weight of polyoxyethylene octylphenyl ether surfactant, 0.02-0.05 parts by weight of sodium hydroxide pH modifier, 0.01-0.03 parts by weight of citric acid scale inhibitor, 0.02-0.04 parts by weight of sodium benzoate preservative, 0.01-0.03 parts by weight of chlorogenic acid anti-salt agent and 10-20 parts by weight of quartz sand proppant; The viscosity modifier is prepared by reacting carboxymethyl cellulose and amino-polyethylene glycol-lipoic acid in a ratio of 1:1.2 to 1.5 and forming an amide bond under the conditions of 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide; The specific preparation method of the viscosity modifier is as follows: The carboxymethyl cellulose and amino-polyethylene glycol-lipoic acid are dissolved in an acetate buffer to prepare a carboxymethyl cellulose solution and an amino-polyethylene glycol-lipoic acid solution, and a magnetic stirrer is used for dissolving, and the temperature is controlled at 50-70° C. until the solution is completely dissolved. Then, 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide are added to the carboxymethyl cellulose solution, and the mixture is stirred and mixed evenly. The pH value of the solution is adjusted with an acetate buffer, and the amino-polyethylene glycol-lipoic acid is added dropwise to the mixed solution, and the stirring is continued. The reaction time is 4-6 hours. After the reaction is completed, unreacted small molecule byproducts are removed by dialysis, and a dialysis bag is used and an acetate buffer is selected as a dialysis medium for dialysis. The dialysis medium is replaced every 2-4 hours until impurities are no longer detected in the dialysate. Finally, the product is concentrated and stored by freeze drying to obtain a viscosity regulator.

2. A polymer suspension for coal rock gas according to claim 1, characterized in that: The mass fraction of the carboxymethyl cellulose solution is 1-5%.

3. The polymer suspension for coal rock gas according to claim 1, characterized in that: The mass fraction of the amino-polyethylene glycol-lipoic acid solution is 2-5%.

4. The polymer suspension for coal rock gas according to claim 1, characterized in that: The pH value of the solution adjusted by the acetate buffer is 4.5-6.

5.

5. The polymer suspension for coal rock gas according to claim 1, characterized in that: The molar ratio of the carboxymethyl cellulose to 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride and N-hydroxysuccinimide is 1:1-2:1-2.

6. The polymer suspension for coal rock gas according to claim 1, characterized in that: The molecular weight cut-off range of the dialysis bag is 5000-10000Da.

7. The polymer suspension for coal rock gas according to claim 1, characterized in that: The specific preparation method is as follows: Sodium hydroxide pH regulator is added to deionized water to adjust the pH value of the water, and then hydroxypropyl guar gum and polyacrylamide are added, and the mixture is heated and stirred at 40-50°C to dissolve for 30-60 minutes until the polymer forms a uniform solution. Borax and a viscosity regulator are added under continuous stirring, and then polyoxyethylene octylphenyl ether surfactant, citric acid scale inhibitor, sodium benzoate preservative and chlorogenic acid anti-salt agent are added in sequence. Quartz sand proppant is added under stirring, and the mixture is fully stirred to obtain a polymer suspension for coal rock gas.

8. The polymer suspension for coal rock gas according to claim 7, characterized in that: The mass fraction of the sodium hydroxide pH regulator is 1-5%, which adjusts the pH value of water to 7-8.

9. The polymer suspension for coal rock gas according to claim 7, characterized in that: The stirring speed when the hydroxypropyl guar gum and polyacrylamide are added is 300-600 rpm, the stirring speed when the polymer forms a uniform solution is 100-300 rpm, the stirring speed when the polyoxyethylene octylphenyl ether surfactant, citric acid scale inhibitor, sodium benzoate preservative and chlorogenic acid anti-salt agent are added in sequence is 100-200 rpm, and the stirring speed when the quartz sand proppant is added is 300-600 rpm.

Citation Information

Patent Citations

  • Application of polyethylene glycol-lipoic acid derivatives as free-radical scavenger and tyrosinase inhibitor

    CN104922691A

  • Preparation and application of dual-sensitivity amphiphilic polysaccharide-doxorubicin conjugate and pharmaceutical composition thereof

    CN105727309A